2016
DOI: 10.1074/jbc.m116.732768
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Golgi-associated DHHC-type Zinc Finger Protein (GODZ)- and Sertoli Cell Gene with a Zinc Finger Domain-β (SERZ-β)-mediated Palmitoylation by Loss of Function Analyses in Knock-out Mice

Abstract: Edited by F. Anne StephensonThe ␥2 subunit of GABA type A receptors (GABA A Rs) is thought to be subject to palmitoylation by both Golgi-associated DHHC-type zinc finger protein (GODZ; also known as DHHC3) and its paralog Sertoli cell gene with a zinc finger domain-␤ (SERZ-␤; DHHC7) based on overexpression of enzymes and substrates in heterologous cells. Here we have further investigated the substrate specificity of these enzymes by characterization of GODZ and SERZ-␤ knock-out (KO) mice as well as double KO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…Because DHHC3 and DHHC7 belong to the same subfamily of PATs with high sequence homology within the CRD (25), it is not surprising that these enzymes may have overlapping substrates. On the other hand, in vivo studies have revealed distinct substrate specificity for these PATs in the mouse brain (35). Knockdown experiments in cultured cells demonstrated that the presence of endogenous DHHC3 is not enough to fully compensate for DHHC7 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Because DHHC3 and DHHC7 belong to the same subfamily of PATs with high sequence homology within the CRD (25), it is not surprising that these enzymes may have overlapping substrates. On the other hand, in vivo studies have revealed distinct substrate specificity for these PATs in the mouse brain (35). Knockdown experiments in cultured cells demonstrated that the presence of endogenous DHHC3 is not enough to fully compensate for DHHC7 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the roles of UL20 and its regulation in vivo are hampered by the essential role of UL20 and the inability of UL20 deletion mutants of HSV-1 to replicate efficiently in vitro or in vivo (3,4,32). Our recent construction of GODZ Ϫ/Ϫ mice (19), however, enabled investigation of the contribution of the GODZ component of the UL20-gK network to HSV-1 infectivity using MEFs derived from these mice, as well as in vivo analysis. In the current study, we demonstrate that HSV-1 replication in MEFs derived from GODZ Ϫ/Ϫ mice is markedly reduced compared with replication in MEFs from control WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…We recently generated a mouse strain lacking GODZ expression (19). Characterization of these GODZ Ϫ/Ϫ mice confirmed that palmitoylation of the ␥2 subunit of GABA A receptors and of a second substrate, a growth-associated protein of 43 kDa that is involved in trafficking of GABA A receptors, was significantly reduced in the brains of ( Fig.…”
mentioning
confidence: 82%
See 2 more Smart Citations